The journey of a Tzotzil-Maya woman of Chiapas, Mexico : pass well over the earth - Eber, Christine Engla (Louann Atkins Temple women & culture series, 2011)
"Most recent books about Chiapas, Mexico, focus on political conflicts and the Indigenous movement for human rights at the macro level. None has explored those conflicts and struggles in-depth through an individual woman's life story. The Journey of a Tzotzil-Maya Woman of Chiapas, Mexico now offers that perspective in one woman's own words. Anthropologist Christine Eber met 'Antonia' in 1986 and has followed her life's journey ever since. In this book, they recount Antonia's life story and also reflect on challenges and rewards they have experienced in working together, offering insight into the role of friendship in anthropological research, as well as into the transnational movement of solidarity with the Indigenous people of Chiapas that began with the Zapatista uprising. Antonia was born in 1962 in San Pedro Chenalhó, a Tzotzil-Maya township in highland Chiapas. Her story begins with memories of childhood and progresses to young adulthood, when Antonia began working with women in her community to form weaving cooperatives while also becoming involved in the Word of God, the progressive Catholic movement known elsewhere as Liberation Theology. In 1994, as a wife and mother of six children, she joined a support base for the Zapatista Army of National Liberation. Recounting her experiences in these three interwoven movements, Antonia offers a vivid and nuanced picture of working for social justice while trying to remain true to her people's traditions."--Publisher's website